On Computation Degree-Based Topological Descriptors for Planar Octahedron Networks. (1st November 2021) - Zhen, Wang; Ali, Parvez; Ali, Haidar; Dustigeer, Ghulam; Liu, Jia-Bao
Abstract : A molecular graph is used to represent a chemical molecule in chemical graph theory, which is a branch of graph theory. A graph is considered to be linked if there is at least one link between its vertices. A topological index is a number that describes a graph's topology. Cheminformatics is a relatively young discipline that brings together the field of sciences. Cheminformatics helps in establishing QSAR and QSPR models to find the characteristics of the chemical compound. We compute the first and second modified K-Banhatti indices, harmonic K-Banhatti index, symmetric division index, augmented Zagreb index, and inverse sum index and also provide the numerical results.